The Effect of Magnesium Sulfate on Sperm Characteristics and Blood Hematology After Testicular Ischemia-Reperfusion Injury in Rats - Saadat Moshkelani (Crescent Journal of Medical and Biological Sciences, 2020)
Objectives: The aim of this study was to investigate the effect of magnesium sulfate (MgSO4 ) administered single intraperitoneally on sperm characteristics after testicular ischemia-reperfusion (IR) injury in the male rats. Materials and Methods: Thirty adult rats were randomly divided into 5 groups: sham operations (group 1), IR (group 2), IR + 125 mg/kg MgSO4 (group 3), IR + 250 mg/kg MgSO4 (group 4), and IR + 500 mg/kg MgSO4 (group 5). Testicular ischemia was achieved by 720 degrees torsion of the left testis for 2 hours. Then, detorsion was performed and reperfusion was induced. One hour after ischemia, three different doses of MgSO4 (125, 250, and 500 mg/kg) were administrated intraperitoneally. The sperm count, motility, mobility, and blood hematology were evaluated. Results: There was a significant increase in sperm count, motility, and mobility in groups treated with MgSO4 compared to the sham group (P<0.05). In addition, lymphocyte count in the sham group significantly increased compared to the IR group (P<0.05). Conclusions: Generally, this study demonstrated that MgSO4 can improve sperm characteristics after testicular IR injury.